2020
DOI: 10.1021/acssuschemeng.0c01630
|View full text |Cite
|
Sign up to set email alerts
|

Facile Construction of Bi2MoO6/Bi/g-C3N4 toward Efficient Photocatalytic Oxidation of Indoor Gaseous Formaldehyde with a Wide Concentration Range under Visible Light Irradiation

Abstract: The removal of formaldehyde (HCHO) has attracted tremendous attention, because the toxicity and volatility of HCHO seriously affect human health. It is urgent to develop a catalyst that can efficiently remove HCHO in indoor conditions. Here, the Bi 2 MoO 6 /Bi/g-C 3 N 4 heterojunction is prepared by a simple hydrothermal approach and subsequently an in situ reduction. The prepared material is used to photocatalytic degrade HCHO from 50 to 1600 ppm under simulated indoor conditions, presenting 96.15% conversion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Notably, the HRTEM image of Bi@Bi 2 MoO 6 shows that two different lattice spacings exist in the sample (Figure 1i). The lattice spacings of 0.315 and 0.328 nm belong to the (131) facet of Bi 2 MoO 6 and the (012) facet of metallic Bi, respectively [16] . Meanwhile, compared with pure Bi 2 MoO 6 (Figure 1e), it is observed that there were many nanoparticles on the nanosheet surface of Bi@Bi 2 MoO 6 (Figure 1h), corresponding to the inset of Figure 1c.…”
Section: Resultsmentioning
confidence: 93%
“…Notably, the HRTEM image of Bi@Bi 2 MoO 6 shows that two different lattice spacings exist in the sample (Figure 1i). The lattice spacings of 0.315 and 0.328 nm belong to the (131) facet of Bi 2 MoO 6 and the (012) facet of metallic Bi, respectively [16] . Meanwhile, compared with pure Bi 2 MoO 6 (Figure 1e), it is observed that there were many nanoparticles on the nanosheet surface of Bi@Bi 2 MoO 6 (Figure 1h), corresponding to the inset of Figure 1c.…”
Section: Resultsmentioning
confidence: 93%
“…[49,260,263] The superfine Bi nanoparticles as a low-cost alternative of charge transfer medium are usually used in the construction of indirect Zscheme nanojunctions because of the good conductivity and SPR properties. [135,360] In addition, Bi-based inorganic materials show great potential in HCHO oxidization because of the band position and high-energy orbital of Bi 6s. For instance, Wu et al successfully constructed a solid indirect Z-scheme nanojunction of Bi 2 MoO 6 /Bi/PCN through in situ reductions to yield Bi NPs (Figure 13D).…”
Section: Research Progress Of Pcn For Voc Removalmentioning
confidence: 99%
“…The electronic structure regulation and heterostructure construction on PCN are rapidly developed to enlarge the exploitation of PCN photocatalysts on VOC removal, showing the importance and development of this field. [ 63 , 106 , 118 , 135 ] Here, we reviewed the catalyst preparation/synthesis, measurements of catalytic activity, and discussion/understanding of the activity enhancement and catalytic mechanism in the VOC photooxidation. Some recently reported PCN‐based photocatalysts with various strategies used in VOC removal are shown in Table 3 .…”
Section: Application Of Pcn In Environmental Catalysismentioning
confidence: 99%
See 2 more Smart Citations